2020
DOI: 10.33506/pjcs.v2i1.808
|View full text |Cite
|
Sign up to set email alerts
|

Peran Pendidikan di Era Milenial

Abstract: Pendidikan merupakan sarana untuk mencapai proses keilmuan yang memadai, namun masih banyak kalangan yang belum memanfaatkan sarana tersebut untuk mengasah dan meningkatkan kapasitas dirinya. Melalui program Pengabdian Kepada Masyarakat (PKM) dalam hal ini tersaji kedalam bentuk seminar dengan tema “Pendidikan Era Milenial untuk Siswa SMP Negeri 7 Tanjung Kasuari Di Kelurahan Suprau Distrik Maladomes Kota Sorong bertujuan agar memberikan informasi kepada siswa/i SMP tentang pentingnya pendidikan dan mudahnya m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
0
3
0
4
Order By: Relevance
“…Furthermore, the participants were also eager to discover the academic and non-academic experiences while studying overseas. This finding is considered relevant with a community program conducted by Saputra et al (2020), who conducted a scholarship workshop partnered with LPDP to Papuan students in order to enhance the students' understanding and awareness of the scholarship opportunities. Saputra et al (2020) also discovered that the participants were highly passionate about the scholarship session, motivating them to pursue a higher degree overseas with funding assistance from the Indonesian government.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, the participants were also eager to discover the academic and non-academic experiences while studying overseas. This finding is considered relevant with a community program conducted by Saputra et al (2020), who conducted a scholarship workshop partnered with LPDP to Papuan students in order to enhance the students' understanding and awareness of the scholarship opportunities. Saputra et al (2020) also discovered that the participants were highly passionate about the scholarship session, motivating them to pursue a higher degree overseas with funding assistance from the Indonesian government.…”
Section: Discussionmentioning
confidence: 98%
“…A high percentage of participants (33.9%) also put a positive response to the relevance of the online workshop to their present situation with 4 of 5 points. Several studies have discovered the importance of scholarship workshop toward university students as the participants of the program (Saputra et al, 2020;Wirawan, 2019). For instance, Saputra et al (2020), who conducted a scholarship webinar to university students in Papua, revealed that the participants responded positively to the event as it can enhance their motivation to pursue a higher degree through financial aid provided by the government through LPDP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guru memanfaatkan WA untuk menunjang kegiatan pembelajaran Daring dengan memanfaatkan berbagai fitur yang tersedia seperti fitur foto, video, dokumen dan video call. Tantangan bagi guru dalam pembelajaran jarak jauh sekarang ini yang berpusat pada jaringan koneksi internet, sehingga guru harus mampu merancang, mendesain dan mengembangkan metode pembelajaran berjalan secara optimal dengan mempertimbangkan karakteristik peserta didik, materi dan melilih media atau aplikasi yang cocok yang digunakan (Saputra et al, 2020).…”
Section: Tahapan Pelaksanaanunclassified
“…Pendidikan merupakan suatu kebutuhan yang dibutukhan oleh manusia untuk mengembangkan segala potensi yang dimiliki oleh setiap individu (Saputra et al, 2020). Hal ini juga dijelaskan secara global dalam Undang-undang No.…”
Section: Pendahuluanunclassified